2016
DOI: 10.1161/strokeaha.115.012424
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial Therapy and Post-Treatment Infarct Volumes

Abstract: Background and Purpose-The goal of reperfusion therapy in acute ischemic stroke is to limit brain infarction. The objective of this study was to investigate whether the beneficial effect of endovascular treatment on functional outcome could be explained by a reduction in post-treatment infarct volume. Methods-The Endovascular Treatment for Small Core and Anterior Circulation Proximal Occlusion With Emphasis onMinimizing CT to Recanalization Times (ESCAPE) trial was a multicenter randomized open-label trial wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…Using the follow-up ASPECTS as a marker of infarct extent, we observed significantly smaller infarct sizes after ET than after IVT in dependent patients. These data corroborate previous findings, albeit mainly in independent patients, in which the final infarct volumes were significantly smaller after ET than after IVT ( 21 , 22 ). Although it has clearly been shown that a reduced final infarct volume only partially mediates the positive effect of ET on clinical outcome ( 21 ), our primary finding of an improved clinical outcome after ET in dependent patients is thus also supported by the imaging data.…”
Section: Discussionsupporting
confidence: 92%
“…Using the follow-up ASPECTS as a marker of infarct extent, we observed significantly smaller infarct sizes after ET than after IVT in dependent patients. These data corroborate previous findings, albeit mainly in independent patients, in which the final infarct volumes were significantly smaller after ET than after IVT ( 21 , 22 ). Although it has clearly been shown that a reduced final infarct volume only partially mediates the positive effect of ET on clinical outcome ( 21 ), our primary finding of an improved clinical outcome after ET in dependent patients is thus also supported by the imaging data.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in agreement with those obtained by Man et al ( 19 ) We found that failure of reperfusion resulted in infarct growth of approximately 50 ml. In a comparable analysis, Zaidi and colleagues found a mean infarct volume in the recanalized vs. non-recanalized of 50 vs. 134 ml, respectively ( 20 ), while the ESCAPE study found a difference between the recanalized and non-recanalized of only 20.5 ml ( 21 ). These studies could only compare the final infarct between reperfusers and non-reperfusers not knowing the initial infarct.…”
Section: Discussionmentioning
confidence: 97%
“…Various post hoc exploratory analyses of the SWIFT PRIME [23] and ESCAPE [24] trials have demonstrated the 24-to 48-h infarct volumes as a strong predictor of 90-day mRS score. However, laterality of the infarction was not observed to be a significant predictor for 90-day clinical outcomes [24].…”
Section: Discussionmentioning
confidence: 99%